Implementasi Six-Sigma pada Produksi Kain Rayon Lebar PT XYZ - Halwa Annisa Khoiri; Yudha Adi Kusuma; Fanny Diantina Aryaningtyas (Performa: Media Ilmiah Teknik Industri, 2024)
PT XYZ is a textile industry company whose products are wide rayon fabric. In the production period from January 2022 to April 2023, the number of fabric produced was 2,347,646 yards and defect fabric was 333,136 or 14.2%. In the production process, this value exceeds the control limit so a lot of fabric has to be reprocessed. The sigma value of the current production process is 3.172, meaning that system improvements need to reduce the number of defective products. This research aims to minimize product defects using the Six Sigma method. The Six Sigma stages in this research are the define stage to identify types of defects and it was found that there were 18 types of defects, the measure stage to determine the largest percentage of defects and calculate the sigma value, the analyze stage to find out the root cause of defects using a fishbone diagram, the improve stage to formulate proposed improvements using the 5W+1H approach, and the control stage to supervise the implementation of proposed improvements using the Poka Yoke method. The proposed improvements based on the 5W+1H method and the Poka Yoke method are cleaning machines in a row and carried out on a scheduled basis, rescheduling the number of workers per shift to reduce worker negligence, scheduling machine repairs, providing regular training to workers, and adding lighting in the room. production. After implementing this proposed improvement, it is hoped that can increase the sigma value of the production process carried out.